55 Nursing care initiative to assist individualized care plans for the dying patient. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Johnson, Helen
Abstract : Background: The priorities of the dying patient should be a priority of the healthcare team caring for them. To facilitate this, effective and open communication is key. The aim of this initiative was to focus on patients' priorities and to enhance care for patients and those important to them. Methods: CQC reports highlighted initiatives used in palliative care settings. Discussions with colleagues brought out recurrent themes – namely privacy and practical support for family members. Relevant publications were also discussed. Results: The use of an End of Life symbol is prevalent in other hospitals, displayed once a patient has died. On this unit due to factors such as withdrawal of treatment, patient deaths can be expected, therefore, the use of a symbol during this period to alert the multidisciplinary team (MDT) – including of course domestic staff – minimize unnecessary interruptions and enhance the patients (and family's) overall care was implemented. Policy, guidelines and consent forms were developed and agreed upon with the help of the wider MDT. Teaching for all staff commenced, copyright obtained from the Irish Hospice Foundation for the use of this particular symbol. The first audit received a response rate of 17% (from the MDT). This showed 91% reported minimized disruption, 82% felt family were cared for and 100% found it useful. Conclusions: The over-riding comment from the patient, their families and friends when consenting for use of the symbol was 'anything as long as it means peace and quiet'. The worry that the symbol would stop people entering was unfounded. It enhanced the essential care and enabled the patients' individual preferences to be carried out. Feedback obtained through conversations with relatives and questionnaires completed by staff has been overwhelmingly positive.